The oncogenic roles of TRPM ion channels in cancer - Wong, KK; Banham, A; Yaacob, N; Husna, SMN (Wiley, 2019)
Transient receptor potential (TRP) proteins are a diverse family of ion channels present in multiple types of tissues. They function as gatekeepers for responses to sensory stimuli including temperature, vision, taste, and pain through their activities in conducting ion fluxes. The TRPM (melastatin) subfamily consists of eight members (i.e., TRPM1–8), which collectively regulate fluxes of various types of cations such as K+, Na+, Ca2+, and Mg2+. Growing evidence in the past two decades indicates that TRPM ion channels, their isoforms, or long noncoding RNAs encoded within the locus may be oncogenes involved in the regulation of cancer cell growth, proliferation, autophagy, invasion, and epithelial–mesenchymal transition, and their significant association with poor clinical outcomes of cancer patients. In this review, we describe and discuss recent findings implicating TRPM channels in different malignancies, their functions, mechanisms, and signaling pathways involved in cancers, as well as summarizing their normal physiological functions and the availability of ion channel pharmacological inhibitors.